Lhermitte Sign as a Presenting Symptom of Thoracic Spinal Pathology: A Case Study - Adam Hills; Mazen Al-Hakim (Case Reports in Neurological Medicine)
A 54-year-old male with ankylosing spondylitis presented with complaints of progressively worsening bilateral leg weakness and difficulty ambulating of 2-week duration. He also felt a sharp, electric, shock-like sensation radiating from his lower back into his legs upon flexing the trunk. There was no history of trauma or other inciting events within the 2 weeks prior to presentation. Thoracic MRI at this visit showed a three-column fracture at T11-T12. He underwent spinal fusion surgery and within 2 days after surgery the radiating electrical sensation with spinal flexion had completely resolved.